2017
DOI: 10.1002/polb.24555
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic insights on the LCST behavior of PMEO2MA in water by molecular dynamics simulations

Abstract: Fully atomistic molecular dynamics simulations of poly(2-[2-methoxyethoxy]ethyl methacrylate) (PMEO 2 MA) in water at temperatures below and above its lower critical solution temperature (LCST) were performed to improve the understanding of its LCST behavior. Atomic trajectories were used to calculate various structural and dynamic properties. Simulation results show that PMEO 2 MA undergo a distinct coil-to-globule transition above LCST. Detailed analyses of the number of first hydration shell water molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
5
6
0
Order By: Relevance
“…Meanwhile, the backbone conformation of the 5-mer POEGMA 300 block does not change significantly. These results are consistent with the findings of our previous studies; 44,45 that is, 5-mer polymer length is not sufficient for a single POEGMA chain to provide LCST transition under our simulation conditions.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Meanwhile, the backbone conformation of the 5-mer POEGMA 300 block does not change significantly. These results are consistent with the findings of our previous studies; 44,45 that is, 5-mer polymer length is not sufficient for a single POEGMA chain to provide LCST transition under our simulation conditions.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The average R g values calculated over the last 50 ns of each temperature are given in the Supporting Information, Table S1. These results are quite close to our previous POEGMA homopolymer studies. , For example, for the 20-mer PMEO 2 MA homopolymer, we found the average R g as 12.96 and 11.06 Å at 290 K ( T < LCST) and 330 K ( T > LCST), respectively. In this study, we found the average R g of the PMEO 2 MA block in 20/5 and 20/20 copolymers as 13.80 and 12.87 Å at 290 K and 12.12 and 11.15 Å at 330 K, respectively.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Atomistic studies explain the role of H-bonds in driving chain conformation changes (e.g., polyaminoamide dendrimer conformations in ref ) and phase transitions in polymer solutions. For example, in the latter case of phase transitions in polymer solutions, atomistic MD simulation studies have shown the extent of H-bond interactions between the polymer (e.g., poly­( N -isopropylacrylamide)) and water, within the polymer chain and between polymer chains, and below and above phase transitions. , In polymer nanocomposites, the impact of H-bonds between the surface of a particle and the polymer chains in the matrix (e.g., graphene oxide and poly­(vinyl alcohol), modified silica and poly­(dimethylsiloxane)) on the overall binding energies between the various components have been calculated using atomistic simulations. These have been used to explain the observed improvements in the mechanical properties (e.g., frictional stress, storage modulus) of the polymer nanocomposites.…”
mentioning
confidence: 99%